Assets need audiences: How venture capitalists boost valuations by recruiting investors to asset circles - Dave Elder-Vass (Finance and Society, 2021)
Narratives and conventions have received considerable attention in recent discussions of the valuation of financial assets. Narratives and conventions, however, can only be effective to the extent that they attract and persuade audiences, and this article makes the case for paying more attention to those audiences. In particular, the article argues that financial assets can only be established as assets if there is a group of potential investors that has been persuaded to accept them as such: to take them seriously as potential investments. The article coins the term asset circles to refer to such groups and supports the argument with a discussion of venture capital and its role in the production of unicorns: private companies with extraordinary valuations. Venture capital firms may be thought of as value entrepreneurs, and much of the venture capital process is oriented towards constructing both value narratives for the companies they invest in and asset circles prepared to accept those value narratives. Their aim in these processes is a profitable exit, in which the venture capital firm converts its investment back into cash at a considerable profit through either an acquisition or a flotation.
Keywords: 300; Venture capital; valuation; IPO; conventions; asset circles; assetisation